Implications of diversification in coffee crop on four parasitoid families - Tomazella, Vitor Barrile (2020)
The simplification of the agriculture using mainly monoculture imply in huge loss to diversity and other ecological services, such as pest control. Coffee crop, in Brazil, is typically produced under this system of production with large areas of monoculture. But, in southern Minas Gerais, even the production being monocultural, the local landscape is mainly a mosaic of vegetation fragments and, these vegetation improve the diversity of parasitoids, a regional aspect that helps the improvement of the diversification. Another way of diversification is the utilization of shade trees intercropped with the coffee, that also have lot of benefits, such as increase in the parasitoids diversity. By general, many works showed these increments to all families of parasitoids, but only few works were conducted aiming the beneficial families only. Our work goal was to figure out what is the contribution of native vegetation, diversified coffee and shade in coffee in the diversity, abundance and richness of four parasitoid families that have many important coffee pests parasitoids. This work was carried in two farms on southern of Minas Gerais, Brazil, on with coffee crop intercropped with different tree species, being them, Avocado, Mangium, Macadamia, Cedar and Teak and a native surrounding vegetation, and another with a shaded coffee and a full sun coffee. We collect parasitoids at the diversified coffee, the one intercropped, at native vegetation and a monocultural coffee crop. At the second, we collected parasitoids in the shaded coffee and full sun coffee. In both cases, the collects were carried from 2016 to 2018, every three months, utilizing yellow pan traps that stayed at the field for a period of 48 hours. The insects were taken to the Laboratório de Controle Biológico Conservativo of Universidade Federal de Lavras to be identified at morphospecies. At the first farm, we analysed two things, the first, was the influence of the trees used to diversify the coffee crop on the four families of parasitoids and if there were difference in these diversity from a monoculture of coffee; the second was to find differences between the intercropped coffee, the monoculture coffee and the native vegetation on the same four parasitoids families. On the second farm, we analysed the effect of shaded coffee and full sun coffee on the community of the same four parasitoid families. Our results, for the first farm and the first case, were that the Avocado (0.19) and Full Sun (0.07) coffee showed similar results for diversity and both lower than the founds for the other plants: Mangium (0.57), Cedar (0.42), Macadamia (0.38) and Teak (0.32). For the second case at the first farm we found a difference in all three treatments, being the Diversified (1.64), Native (1.09) and Monoculture (0.07) all different with the diversified being the greater. For the second farm, we found a well visible difference from shaded (0.59) and full sun (0.32) diversity. We this, we concluded that, the diversification, improve the diversity of the parasitoid families and also, the shade at coffee plantation brings benefits to it.